Implementation Of Merdeka Belajar-Kampus Merdeka And Response Of Physics Education Students At Syiah Kuala University - Vini Asnidar; Nurulwati; Abdul Hamid; Ichsan; Zahrul Fuadi; Mariati (Jurnal Serambi Ilmu, 2024)
The satisfaction of students towards the Community Service Learning Program (CSLP) has become a significant focus for the university, prompting a thorough evaluation of strategies in each program. The goal is to enhance student satisfaction with the quality of CSLP services at USK Unggul University. The objective of this research is to describe the response of Physics Education students at the Faculty of Teacher Training and Education, Syiah Kuala University, regarding the implementation of Independent Learning-Campus Independent (ILCI). This research employs a qualitative approach through questionnaires and interviews, with a sample of 57 respondents who completed the questionnaire and 10 of whom were interviewed. The response of Physics Education students from the Faculty of Teacher Training and Education, Syiah Kuala University, who participated in the Independent Learning-Campus Independent program, yielded a satisfaction rate of 71%. Keywords: USK Unggul CSLP, Satisfaction Response.